PEMANFAATAN AIR ASAM TAMBANG BATUBARA SEBAGAI SUMBER ENERGI LISTRIK ALTERNATIF - Fatimah Islamunisa; Bohari -; Aman Sentosa Panggabean (Jurusan Kimia FMIPA UNMUL, 2018)
The research about utilizing Acid Mine Drainage (AMD) as source of electrical energy has done. The variables of the observations made in the influence of electrode, number of cells and the working time of the cell. The results showed that the electrode, the number of cells and the working time of the cell affect the potential value of cells. The pair of electrodes of the metal cooper (Cu), Zinc (Zn), Carbon (C) have been varied showed the potential value of the most high by using a pair of electrodes C-Zn amounting to 1.68 V. More the number of cells that are used the higher the potential value that is produced, where the use of cells from 1 until 5 consecutive potential values of the cells produced are 1.57 V; 3.28 V; 4.90 V; 6.57 V; 8.20 V. The working time of the cell the longer it is used the more reduced the potential value of what is produced, where from 0 h, 3 h, 6 h, 9 h, 12 h and 15 h respectively the potential value of the cells produced are 1.63 V; 1.61 V; 1.59 V; 1.57 V; 1.56 V.